ANALISIS YURIDIS PERNIKAHAN BEDA AGAMA DI INDONESIA DITINJAU DARI SDGs PEREMPUAN - ica, Annisa; Nakita Wahdah, Azzahra (UIR Law Review, 2025)
Interfaith marriage in Indonesia is a complex issue involving law, religion, and human rights, especially related to gender equality and women's empowerment (SDGs Number 5). This study aims to analyze the impact of interfaith marriage law on the legal status of husbands, wives, and children, and its implications for SDGs Number 5. The research method used is normative juridicial with a legislative approach and a conceptual approach. Primary data in the form of laws and regulations, SEMA, and expert opinions, while secondary data comes from books, journals, and relevant internet sources. The results of the study show that interfaith marriage in Indonesia faces legal obstacles because the Marriage Law requires the validity of marriage based on each person's religion, while the majority of religions in Indonesia prohibit it. This has an impact on the unclear legal status of husbands, wives and children, the vulnerability of women in terms of inheritance rights, maintenance, and child care, and is contrary to the principles of gender equality and women's empowerment as promoted by SDGs Number 5. SEMA No. 2 of 2023 which prohibits courts from recording interfaith marriages further strengthens this discrimination. Inclusive and gender-sensitive marriage law reforms and interfaith dialogue are needed to bridge differences and protect women's rights in interfaith marriages. Keywords: Interfaith Marriage, SDGs, Women